Edukasi dan Pelayanan Tapping Menurunkan Gejala Hipertensi pada Karyawan PT Tirta Investama - Surasta, I Wayan; Suardana, I Ketut; Achjar, Komang Henny (Sekolah Tinggi Ilmu Kesehatan KESDAM IX/Udayana, 2024)
Metabolic syndrome is a symptom of metabolic disorders suffered in conditions of prosperity, if you are obese (overweight) accompanied by hypertension and increased blood sugar levels as well as hypercholesterolemia and increased uric acid. PT Tirta Investama employees with increased welfare from 450 employees through medical check-ups at Siloam Hospital as a referral hospital, 200 of them experienced symptoms of hypertension and obesity. Of the 200 people, due to company policy, HRD decided to take 100 people. It is on this basis that community service is carried out which aims to provide knowledge about how to treat metabolic syndrome, carry out blood pressure checks, examine abdominal circumference and provide Tapping educational services. Tapping is a holistic, complementary nursing action to reduce emotions and stress. Complementary acupressure nursing services are also provided. The method of activity carried out is blood pressure screening, measuring body weight, height and measuring abdominal circumference. Then Tapping education is carried out and the application practice is carried out step by step until the participants can actually carry it out independently. After 2 weeks of activity, 100 participants were evaluated by repeating the Tapping procedure independently. The community service participants were able to do it correctly, and said that the symptoms of headaches, ringing in the ears had decreased and they felt calmer and emotionally stable, and awareness emerged to change their lifestyle to be healthy. So that community service activities are still needed by employees, the follow-up from this community service is explained to employees who have participated in this activity to be able to pass on knowledge about Tapping to other employees and this activity is carried out independently as well as for their families.